The Energy-Saving Control Criterion for Impact Crushing Machines - Chausov S.; Sabo A.; Popova I.; Budko V. (Problems of the Regional Energetics, 2023)
The purpose of the article is to substantiate the use of a new criterion for controlling the grinding technological process to improve the use of electrical energy. The subject of the study is the process of using electrical energy in impact grinding machines. The set goal is achieved by solving the following problems: analyzing the energy of the grinding process, determining the parameters of raw materials and operating modes of the electric drive that affect the efficiency of electrical energy usage. Based on theoretical research, a mathematical model of energy consumption in grinding processes has been developed. Analytical studies of the resulting mathematical model showed the nonlinear extreme nature of the specific energy consumption of the grinding process with changing raw material parameters and operating modes. This creates the prerequisites both for using specific electrical energy costs as a control criterion and for the use a controlled electric drive to achieve maximum energy savings. The most important result is that the operating modes of grinding machines could be established by more efficient use of electrical energy. The significance of the work lies in the fact that by adapting the operating modes of the electric drive to the current parameters of the raw materials and the state of the equipment make possible to reduce the specific electrical energy consumption up to 15% and this is the basis for using a criterion based on specific costs in control systems for technological processes with grinding impact machines. For further application of the obtained results it is necessary to conduct experimental studies to confirm the increase in the efficiency of electrical energy use.